Islamic Religious-based Local Content Curriculum in Madrasah Tsanawiyah: A Multi-Site Study in Pekan Tanjung Pura - Anggraini, Pauli; Asari, Hasan; Nst, Sahkholid (Lembaga Penelitian dan Pengabdian Masyarakat Institut Agama Islam Al-Khairat Pamekasan, 2023)
This study aims to analyse the similarities and differences in the planning, implementation, and evaluation of the religious-based local content curriculum in three different MTs, namely MTs Jam'iyah Mahmudiyah Tanjung Pura, MTs Yaspend Muslim Pematang Tengah, and MTs Pondok Pesantren Islam Shuffah Hizbullah Al-Fatah. The methods used are cross-site analysis, purposive sampling, internal sampling, time sampling, and data collection techniques using interviews, observation, and documentation. The results showed similarities in objectives, principles, scope, steps, materials, and evaluation of the local content curriculum, which aims to preserve Islamic values and improve students' understanding and religious practices. Differences are seen in the types of local content used, namely Malay Arabic script, Qur'an memorisation, and Qur'an memorisation, emphasising pesantren. This difference reflects the needs and local context of each madrasah. This study provides an overview of the practice of religion-based local content curricula in MTs and its implications for forming students' character and religious identity. It also suggests further research on the long-term impact of differences in implementing the local content curriculum on students' character-building and religious identity.